[OP.2A.05] LANOSTEROL SYNTHASE GENE POLYMORPHISMS IMPACT THE DECLINE IN RENAL FUNCTION AMONG HYPERTENSIVE PATIENTS. (September 2017) - Fontana, S.; Lanzani, C.; Simonini, M.; Citterio, L.; Carpini, S. Delli; Casamassima, N.; Messaggio, E.; Tentori, S.; Iatrino, R.; Zagato, L.; Manunta, P.
Abstract : Objective: Cholesterol is an essential component of mammalian cell membranes and serves as a precursor for bile acids and various steroid hormones. Lanosterol, the first committed intermediate in cholesterol biosynthesis, is coded by the Lanosterol Synthasis gene (LSS) with a missense polymorphism that affects EO biosynthesis in adrenocortical cells. Recently, we reported that the LSS AA genotype is associated with salt-sensitive hypertension. Exposure to increased circulating EO causes glomerular damage, and is a risk factor for acute kidney injury. In this report, we explore the importance of LSS in the progression of chronic kidney disease (CKD). Design and method: A cohort of 338 naïve hypertensive patients (f 162, m 176, age 42.7 8.41 years), were enrolled in a prospective follow-up study (5.32 ± 4.37 years) in which blood pressure values were kept at goal with ACEi plus diuretic and, when needed, a Ca2+ channel antagonist. Results: Blood pressure values (SBP/DBP) after 4.6 years of follow-up were at target for all patients with no difference according to genetic polymorphism (LSS AA 138/85 AC 137/87 CC 137/87, respectively). The slope in eGFR (CKD-EPI) was 1.43 ± 0.47 ml/1.73 m 2 /yr in the whole studied population. When analysed according to the LSS genotype, the decline in renal function was double in the AA homozygotes (LSS AA -2.01 ± 2.4 vs CC 2.23 ± 1.20 ml/1.73 m 2 /yr; p = 0.024). The impact of such LSS polymorphism was also reflected in renal survival analysis (p = 0.001). Figure. No caption available. Conclusions: Our findings further support the role of LSS polymorphisms in the progression of CKD. This metabolic pathway may accelerate the decline in renal function via its effects on glomerular podocyte and tubular components.